Interfragmentary Compression Forces Vary Based on Scaphoid Bone Screw Type and Fracture Location. (May 2019) - Patel, Samik; Tiedeken, Nathan; Qvick, Lars; Debski, Richard E.; Kaufmann, Robert; Fowler, John R.
Background: The objective of this study was to determine the interfragmentary compression forces generated in a foam model as a function of headless compression screw type (fully threaded and central threadless) and fracture location.Methods: Eighty-eight polyurethane foam models were fixed across a simulated transverse fracture with either a fully threaded screw or a central threadless screw. The location of the transverse fracture varied along the length of the foam model in 2 mm increments for 11 fracture locations. The force generated at the fracture site upon fixation was utilized to determine the interfragmentary compression. Interfragmentary compression was compared using a paired t test and 2-way analysis of variance, with significance set at P < .05.Results: Interfragmentary compression was found to vary based on fracture location and screw type. The fully threaded screw generated significantly greater compression for fracture locations at 12 mm and 18 mm from the top edge of the foam model, while the central threadless screw generated significantly greater compression for fractures located 2 mm from the top edge of the foam model.Conclusions: The central threadless screw and the fully threaded screw had different fracture locations where maximum compression force occurred. The fully threaded screw generated greater compression force toward the screw center due to greater thread purchase. However, the central threadless screw generated greater compression at the most proximal fracture location due to its greater thread pitch toward the screw head. Maximizing interfragmentary compression may aid in reducing nonunion rates associated with the internal fixation of proximal scaphoid fractures.